2017
DOI: 10.1590/s0102-865020170110000002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of intraperitoneal adhesions related to light-weight polypropylene mesh and type I polymerized and purified bovine collagen coated light-weight polypropylene mesh in rabbits

Abstract: Comparative study of intraperitoneal adhesions related to light-weight polypropylene mesh and type I polymerized and purified bovine collagen coated light-weight polypropylene mesh in rabbits 1 2-Experimental SurgeryActa Cir Bras. 2017;32(11):903-912 AbstractPurpose: To compare the effectiveness of light-weight polypropylene mesh coated with polymerized and purified bovine type I collagen (Surgidry HNB) in the treatment of abdominal wall defect and the degree of adhesion formation. Methods: Two types of polypr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Similar results were found by Garcia et al . 19 in an experimental study with rabbits with polypropylene mesh versus polypropylene with bovine collagen, where animals with only a polypropylene mesh presented a greater surface area of adhesion compromise with intra-abdominal viscera compared to the double-sided mesh. However, the result of the present study differs from the study by Biondo-Simões et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar results were found by Garcia et al . 19 in an experimental study with rabbits with polypropylene mesh versus polypropylene with bovine collagen, where animals with only a polypropylene mesh presented a greater surface area of adhesion compromise with intra-abdominal viscera compared to the double-sided mesh. However, the result of the present study differs from the study by Biondo-Simões et al .…”
Section: Discussionmentioning
confidence: 98%
“…Garcia et al . 19 concluded that the polypropylene mesh, although effective in treating abdominal wall defects, causes an intense inflammatory and foreign body reaction. The appearance of dense and firm adhesions with the intra-abdominal viscera is attributed to this bioincorporation process of the intraperitoneally implanted mesh.…”
Section: Discussionmentioning
confidence: 99%
“…However, this practice has failed to obtain widespread adoptance, probably due to a lack of technique standardization and concerns for mesh-related complications, including chronic pain, prosthesis infection, seroma formation, in addition of increased cost and operative time. Moreover, a survey study by Bloemen et al 21 revealed that only 35% of Dutch surgeons close the abdominal fascia using the recommended 4:1 length suture and 68% didn't change their closure technique since their training, showing that surgeons have some aversion to change their practices.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Хорошо известны трудности, возникающие в ряде случаев при восстановлении глубоких слоев брюшной стенки (задние листки влагалищ прямых мышц живота, брюшина) в ходе операции TAR, что может приводить к прямому контакту эндопротеза с органами брюшной полости на некоторых участках [11]. Моделирование таких операций на лабораторных животных является существенным дополнением для клинического опыта [12]. Вариант использования двух сеток (полипропиленовой и резорбируемой полиглактиновой) исследован в эксперименте с обнадеживающими результатами [11].…”
unclassified